Cloning and overexpression of the DaSOD1 gene from Dioscorea alata improves cadmium resistance in transgenic tobacco plants - Shumei Hua; Hsin-Hung Lin; Zhehong Huang; Mengyao Wang; Qing Li; Shi-Peng Chen (Journal of Plant Interactions)
Minghuai 1 (MH1) is a yam (Dioscorea alata) cultivar characterized by its strong resistance to Cd stress. This study aims to investigate the enzymatic antioxidant system of MH1 under Cd stress. Under Cd treatment, MH1 exhibited an elevation in superoxide dismutase (SOD) activity, while the activities of ascorbate peroxidase, catalase, and peroxidase remained unchanged. A Cu/Zn-SOD gene, DaSOD1, was cloned and found to be up-regulated following Cd treatment. The DaSOD1 gene was further introduced into tobacco plants for functional analysis. Transgenic tobacco seedlings overexpressing DaSOD1 under Cd treatments exhibited increased chlorophyll contents and seed germination rate, while the levels of superoxide anion and malondialdehyde decreased compared to the wild-type plants. This suggests that DaSOD1 overexpression mitigated the negative effects of Cd stress by reducing oxidative damage in plants. Characterization of the SOD activity and its corresponding DaSOD1 gene is expected to improve our understanding of Cd-resistance mechanism in yam plants.